1998
DOI: 10.1007/bf03347305
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dexamethasone treatment of pregnant rats on the development of chromaffin tissue in their offspring during the fetal and neonatal period

Abstract: The aim of these examinations was to determine the influence of dexamethasone (Dx)-treatment of gravid females, on day 16 of gestation on the development of medullary chromaffin tissue of their fetuses and neonatal offspring. In conducting these investigations we used stereological as well as spectrofluorimetric measurements, in 20-day-old fetuses and 1-, 3-, 5-, 7-, 9-, 11-, 13- and 14-day-old neonatal rats. Single Dx-treatment (1.5 mg/kg bw) of the dams led to a significant decrease in body and adrenal weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The influence of a single dexamethasone treatment given to gravid females resulted in the decreased volume of adrenal medulla and the number of chromaffin cells that persisted during the fetal and neonatal period. Decreased proliferation of chromaffin cells during the fetal and early neonatal period was followed by significantly higher values in relation to controls during the second neonatal week, indicating the capacity of the adrenal gland medulla to recover [185]. Multiple dexamethasone doses applied during pregnancy exert a more potent inhibitory effect.…”
Section: Programming Of the Fetal Hypothalamic-pituitary-adrenal Axismentioning
confidence: 94%
“…The influence of a single dexamethasone treatment given to gravid females resulted in the decreased volume of adrenal medulla and the number of chromaffin cells that persisted during the fetal and neonatal period. Decreased proliferation of chromaffin cells during the fetal and early neonatal period was followed by significantly higher values in relation to controls during the second neonatal week, indicating the capacity of the adrenal gland medulla to recover [185]. Multiple dexamethasone doses applied during pregnancy exert a more potent inhibitory effect.…”
Section: Programming Of the Fetal Hypothalamic-pituitary-adrenal Axismentioning
confidence: 94%
“…It is therefore plausible that the perinatal environment during critical periods of life such as gestation and lactation may modify the maturation of the adrenal medulla, with subsequent permanent changes in both the structure and the function of adrenomedullary cells. Putative noxious signals such as hypoxia, glucocorticoid hormones and placental restriction profoundly affect chromaffin cell development in several species (30–32). Using a model of prenatal maternal 50% food restriction diet (FR50), we have demonstrated that maternal undernutrition during the last week of gestation and lactation also markedly impairs the neuroendocrine differentiation of chromaffin cells in male rat at weaning (33).…”
mentioning
confidence: 99%